From The Silent Watchdog to the Lost Watchdog: The Decline of the UK Regional Press' Coverage of Local Government over 40 Years. Issue 2 (3rd April 2021) - Clark, Tor
Abstract : In 1976 David Murphy wrote his critique of the role of the UK regional press in local politics—The Silent Watchdog: The Press in Local Politics. Through the next two decades, local 'papers of record' attempted to report on the activities and decisions of their local councils regularly and diligently but the decline of the regional press in the twenty-first century has rendered Murphy's critique obsolete. This article will look at what was expected of local journalism in the 1970s. It will show what was delivered until the twenty-first century and then look at how local press coverage of local government has declined, raising the scenario of a 'local democratic deficit' 1 whereby local politics in some communities receives little direct coverage, creating a danger of a disconnect between local government and local communities caused by the abandonment of its former role by the regional press.